Optimalisasi Penerapan Sistem Merit pada Pemerintah Kabupaten Nias - Juniso Lase; Odaligoziduhu Halawa; Eliagus Telaumbanua; Emanuel Zebua (Lembaga Pengembangan Kinerja Dosen, 2024)
The merit system in the management of the State Civil Apparatus (ASN) has been introduced in Indonesia since the Dutch colonial era, but the implementation of a structured and modern merit system officially began in the post-independence era, especially when the Republic of Indonesia was just formed. Based on the results of the assessment of the State Civil Apparatus Commission on the measurement of the merit system above, information was obtained that the Nias Regency Government is in the bad category. This study uses a qualitative research approach where qualitative research as a scientific method is often used and implemented by a group of researchers in the field of social sciences, including education. The results of the study show that the implementation of the merit system in the Nias Regency government is currently an important step in building clean, effective, democratic, and trusted governance. Optimizing the implementation of the merit system in the Nias Regency government has a significant impact, including improving organizational performance, better public services, filling key positions by competent individuals, transparency in employee management, and creating a more productive and collaborative work environment.